Intracranial hemorrhage in infants after massaged by a traditional birth attendant - Elisabeth S. Herini; Sunartini Hapsara; S. Yudha Patria (Paediatrica Indonesiana, 2007)
Background The overall incidence of birth related injuries declineswith the improvement in obstetrics. However, the incidence ofhead trauma in infants after massaged by a traditional birthattendant (TBA) is still unknown.Objective To study the characteristics of intracranial hemorrhagein infants after massaged by a TBA.Methods A retrospective study was conducted in Sardjito Hospital,Yogyakarta, Indonesia between October 2001 and May 2005.Infants with intracranial hemorrhage after massaged by a TBAwere included. Data on patients’ demography, history of massagingby TBA, clinical presentation, and injury characteristics such asanemia, clotting time (CT), bleeding time (BT), prothrombin time(PT) and activated partial thromboplastin time (APTT) werenoted. Computed cranial tomography (CT) scans were performed.Results A total of seven infants were diagnosed with intracranialhemorrhage after massaged by a TBA. There were four malesand three females (mean age 46 days; range 27-60 days). Allinfants were referred to Sardjito Hospital, Yogyakarta, Indonesiawith bad condition and anemia; mean hemoglobin level was 5.5g/dl (range 3.7-8.3 g/dl). All infants presented with seizures.Coagulation screening showed normal results in five patients. Theremaining patients had a prolonged CT and PT. CT scan showedsubdural hemorrhage in four patients, intracerebral hemorrhagein four, epidural hemorrhage in two, and subarachnoid hemorrhagein one. Two patients had chronic hemorrhage, while the rest hadacute hemorrhage. Four of them underwent craniotomy, twopatients were under an observation only, and one patient was nottreated due to parental refusal. Six patients survived and the onewho refused to be treated died.Conclusions The parents, midwives, and doctors have to be awareof head massaging since it may harm infants.